(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The essay criticizes the US Supreme Court’s Dobbs ruling on abortion. It contrasts the rigidly originalist theoretical approach of the judgement with the dissenting opinion of Breyer, Sotomayor and Kagan, which focuses on women’s freedom, equality and self-determination in the area of reproductive rights. After also criticizing the balance contained in sentence no. 27/1975 of the Italian Constitutional Court, it proposes some reform hypotheses of law no. 194/1978, taking into account the 2022 WHO Abortion care guideline.